Delamanid-containing regimens and multidrug-resistant tuberculosis: A systematic review and meta-analysis - Nasiri, Mohammad Javad; Zangiabadian, Moein; Arabpour, Erfan; Amini, Sirus; Khalili, Farima; Centis, Rosella; D'Ambrosio, Lia; Denholm, Justin T.; Schaaf, H. Simon; van den Boom, Martin; Kurhasani, Xhevat; Dalcolmo, Margareth Pretti; et al. (International journal of infectious diseases, 2022)
•MDR-TB is difficult to manage; updated clinical guidance of new drug use is needed•No recent systematic review/meta-analysis on delamanid (DLM) is available•In observational studies including DLM (591 patients) the success rate was 80.9%•In experimental studies including DLM (391 patients) the success rate was 72.5%•Few adverse events attributable to DLM were reported Multidrug-resistant tuberculosis (MDR-TB) is a life-threatening condition needing long poly-chemotherapy regimens. As no systematic reviews/meta-analysis is available to comprehensively evaluate the role of delamanid (DLM), we evaluated its effectiveness and safety. We reviewed the relevant scientific literature published up to January 20, 2022. The pooled success treatment rate with 95% confidence intervals (CI) was assessed using a random-effect model. We assessed studies for quality and bias, and considered P<0.05 to be statistically significant. After reviewing 626 records, we identified 25 studies that met the inclusion criteria, 22 observational and 3 experimental, with 1276 and 411 patients, respectively. In observational studies the overall pooled treatment success rate of DLM-containing regimens was 80.9% (95% CI 72.6-87.2) with no evidence of publication bias (Begg's test; P >0.05). The overall pooled treatment success rate in DLM and bedaquiline-containing regimens was 75.2% (95% CI 68.1-81.1) with no evidence of publication bias (Begg's test; P >0.05). In experimental studies the pooled treatment success rate of DLM-containing regimens was 72.5 (95% CI 44.2-89.8, P <0.001, I2: 95.1%) with no evidence of publication bias (Begg's test; P >0.05). In MDR-TB patients receiving DLM, culture conversion and treatment success rates were high despite extensive resistance with limited adverse events.